O vírus sincicial respiratório induz NETose clássica ROS-dependente através da ativação de PAD4 e das vias de necroptose - Muraro, Stefanie Primon (2018)
Respiratory syncytial virus (RSV) is a major cause of diseases of the respiratory tract in humans being mainly associated with bronchiolitis, chronic obstructive pulmonary disease (COPD) and asthma exacerbation. RSV infection occurs primarily in pulmonary epithelial cells and, once infection is established, an innate immune response is triggered and mainly neutrophil recruitment is induced. Neutrophils can extrude neutrophil extracellular traps (NETs) capable of entrapping and inactivate a multitude of microorganisms because of its composition and due to the stringy nature of DNA fibers. Recently, was demonstrated that RSV particles and its fusion (F) protein were able to induce the release NETs coated with neutrophil elastase and myeloperoxidase, both antimicrobial peptides. Also, was observed that the excessive formation of NETs can have negative consequences to the host, such as airway obstruction during RSV infection. Therefore, the aim was to evaluate the mechanisms involved in NET formation induced by RSV infection of neutrophils, alveolar epithelial cells (A549) or lung fibroblasts (MRC5). Human neutrophils were infected with RSV and were able to induce NETs release only after 3 hours of stimulation indicating classical NETosis. Next was characterized NETs formation during infection associating DNA extrusion with MPO, NE and F protein of RSV. Was also observed NADPH oxidase and PAD4 dependence and PI3K/AKT, ERK and p38 MAPK pathways during infection. The inhibition of these signaling pathways, PAD4 and ROS production abolished NET formation. Considering a possible involvement of necroptosis during NETs production, were tested MLKL and RIPK inhibitors and evaluated LDH release in the supernatant of infected neutrophils. Neutrophils released LDH and depend on necroptosis induction to produce NETs. Likewise, neutrophils were co-cultured with A549 or MRC5 cells infected with RSV. Both A549 and MRC5 cells triggered NET release by human neutrophils in a virus concentration-dependent manner, the opposite occurs when used UV-inactivated virus. Briefly, RSV induces the classical/ROS-dependent NETosis by human neutrophils, and this effect relies on specific kinases activity. Furthermore, neutrophils are able to recognize pulmonary cells infected by RSV, releasing NETs. Thus, NETs release control could be crucial for minimizing tissue inflammation caused by RSV infection.